Algeria's National Strategy for the Blue Economy: Prospects and Challenges for Its Operationalization (Journal of Informatics Education and Research, 2026)
This study aims to highlight the importance of the blue economy as a global development trend, by clarifying the theoretical context of the blue economy and its affiliated sectors, then shedding light on the reality of the blue economy in Algeria, followed by an examination of the National Blue Economy Strategy, issued with financial support from the European Union, and the challenges facing its implementation. This is done by investigating how Algeria can exploit its maritime space and water resources in its drive to crystallize a new strategic development model under the umbrella of the blue economy concept, in order to diversify the Algerian economy and push growth forward.